So-oc Resettlement Project and its effects on general well-being of its beneficiaries - Deslate, Jeanette
The descriptive research determined the effects of Iloilo City Local Government Unit's management of the So-oc Resettlement Project (SRP) on the general well-being of its beneficiaries. This was gauged by comparing the relocatees health conditions, livelihood, and household income before and after relocating to the SRP. Two hundred forty-eight (248) out of six hundred forty-six (646) heads of the beneficiary families responded to the interview schedule formulated by the researchersTo describe the socio-economic profile of the beneficiaries, frequency counts, tables, percentages, and means were employed, together with the Spearman Rank Correlation Coefficient to interpret the resultsThe findings showed that the socio-economic status of the household beneficiaries has actually improved after relocation which is indicated by the increase in the average household income, as well as in the number of household assets possessed and decrease in the number of those without livelihood. Public amenities provided are health services, water source, for washing and drinking, power supply, livelihood assistance, and road networksAmong these, health services ranked the lowest due to unavailability and insufficiency of facilities and awareness on available health services. Furthermore, the results also revealed that a number of project beneficiaries caught cough and fever after relocation. The major perceived causes of these are flooding, proximity to the dumpsite, unclean water, and limited access to health services. Unfortunately, no conclusive or direct connection was established in the study. It was also found out that unemployment decreased after relocationGenerally, the respondents assess their well-being as better now than prior to their transfer to the So-oc Resettlement Project site. They enjoy better services in terms of water and power supply, drainage and sanitation facilities, peace and security, and recreation. Therefore, The So-oc Resettlement Project Management was found to significantly affect the general well-being of its beneficiaries. The LGU's role in the project management, in terms of supervision and provision of public services further enhanced the well-being of the beneficiaries. Lastly, specific measures need to be established to mprove the well-being of the SRP beneficiaries.